A type III-A CRISPR–Cas system mediates co-transcriptional DNA cleavage at the transcriptional bubbles in close proximity to active effectors. Issue 13 (1st July 2021) - Lin, Jinzhong; Shen, Yulong; Ni, Jinfeng; She, Qunxin
Abstract: Many type III CRISPR–Cas systems rely on the cyclic oligoadenylate (cOA) signaling pathway to exert immunization. However, LdCsm, a type III-A lactobacilli immune system mediates efficient plasmid clearance in spite of lacking cOA signaling. Thus, the system provides a good model for detailed characterization of the RNA-activated DNase in vitro and in vivo . We found ATP functions as a ligand to enhance the LdCsm ssDNase, and the ATP enhancement is essential for in vivo plasmid clearance. In vitro assays demonstrated LdCsm cleaved transcriptional bubbles at any positions in non-template strand, suggesting that DNA cleavage may occur for transcribing DNA. Destiny of target plasmid versus nontarget plasmid in Escherichia coli cells was investigated, and this revealed that the LdCsm effectors mediated co-transcriptional DNA cleavage to both target and nontarget plasmids, suggesting LdCsm effectors can mediate DNA cleavage to any transcriptional bubbles in close proximity upon activation. Subcellular locations of active LdCsm effectors were then manipulated by differential expression of LdCsm and CTR, and the data supported the hypothesis. Strikingly, stepwise induction experiments indicated allowing diffusion of LdCsm effector led to massive chromosomal DNA degradation, suggesting this unique IIIA system can facilitate infection abortion to eliminate virus-infected cells.